Effect of calcium on the osmotic dehydration kinetics and quality of pineapple - Silva, Keila S. [UNESP]; Fernandes, Milena A. [UNESP]; Mauro, Maria A. [UNESP] (Elsevier B.V., 2014)
The effects of the sucrose and calcium lactate concentrations on the osmotic dehydration kinetics of pineapple, and the diffusivity of each component were investigated. The color, water activity, texture and fruit composition were also evaluated. Osmotic dehydration was carried out using 40% and 50% sucrose solutions with added 0%, 2% or 4% calcium lactate for 1, 2,4 and 6 h of processing time. In general, the gain in calcium was greater in samples submitted to solutions with higher sucrose and calcium lactate concentrations. The greatest calcium contents (approximate to 90 mg/100 g) were reached after 6 h of impregnation in both 40% and 50% sucrose solutions containing 4% calcium lactate. The addition of calcium to the osmotic solution reduced the water content of the product and solute incorporation rate, inhibiting sucrose impregnation and increasing process efficiency. The addition of 4% calcium lactate to the solution increased all diffusivities in comparison to the addition of 2% but not in relation to treatments with no added calcium. Calcium impregnation did not influence the color of the product or the value for stress at rupture, as compared to raw pineapple. The diffusion coefficients presented in this work permitted the selection of the appropriate sucrose and calcium concentrations and the calculation of the processing time to give the desired product composition. (c) 2014 Elsevier Ltd. All rights reserved.
Keywords: Diffusion coefficient; Impregnation; Calcium; Pineapple; Osmotic dehydration